THE SUBJECT "FUNDAMENTALS OF CONDUCTING RESEARCH ACTIVITIES IN THE PROFESSIONAL FIELD" AS AN IMPORTANT MEANS OF FORMING RESEARCH SKILLS OF UNDERGRADUATE STUDENTS (Education in the 21st Century, 2025)
The higher education system in the Republic of Armenia is characterized by the implementation of reforms aimed at developing education in accordance with national priorities and international standards. This is especially important in the bachelor's degree program, where the role of research skills and abilities of future specialists is particularly emphasized. Although many academic disciplines consider the issues of organizing students' research activities and forming their relevant skills and abilities. However, this is often irregular in nature and does not fully provide students with a systematic and comprehensive understanding of how research activities are organized. Therefore, the academic subject "Fundamentals of Conducting Research Activities in the Professional Field" was introduced. Effective teaching and the achievement of outcomes are largely determined, undoubtedly, by the correct choice of teaching principles and methods. This is what determines the relevance of this article.The purpose of the research is to generalize and analyze the experience of teaching the academic subject "Fundamentals of Conducting Research Activities in the Professional Field", to identify the most effective principles and methods that contribute to the formation of students' research skills and abilities.The scientific novelty lies in refining the principles and methods of teaching the academic subject "Fundamentals of Conducting Research Activities in the Professional Field" based on the generalization of teaching experience and their application, aimed at increasing student motivation and developing students' research skills and abilities.Based on the analysis of scientific literature and teaching experience, conclusions were drawn that for effective teaching of this subject, it is necessary to combine various principles and methods, take into account the difficulties students encounter during the learning process, and provide them with the necessary methodological assistance. The introduction of this subject certainly contributes to the formation of students' research skills and interest in scientific activities.
Keywords: research skills and abilities; general didactic and organizational and methodological principles; traditional, active and interactive methods; learning stages; outcomes